Prophylaxis of implant-related infections by local release of vancomycin from a hydrogel in rabbits - Boot, Willemijn; Vogely, H. C.; Nikkels, P. G. J.; Pouran, B.; van Rijen, M. H. P.; Ekkelenkamp, M. B.; Hänsch, Gertrud Maria; Dhert, W. J. A.; Gawlitta, D. (European cells & materials, 2020)
Local prophylaxis with antibiotic-loaded bone cement is a successful method to prevent post-operative infections in patients receiving orthopaedic implants. No comparable method is available for uncemented implants. Therefore, a hydrogel consisting of hyaluronic and polylactic acids was evaluated in a rabbit model for delivery of antimicrobial agents to prevent post-operative infections. In a pilot study, the suitability of the in vivo model was assessed by testing the hydrogel as carrier material for antimicrobial agents. In the main study, the antimicrobial-agent-loaded hydrogel was evaluated for infection prophylaxis. Rabbits received a titanium rod intramedullary in the tibia after contamination with Staphylococcus aureus. The rods were coated with unloaded hydrogel (Gel), hydrogel loaded with 2 % (Van2) or 5 % vancomycin (Van5), bioactive glass (BAG) or N-acetyl-L-cysteine (NAC). To analyse the infection severity after 28 d, histopathological, bacteriological, micro-computed tomographic and haematological analyses were performed. In the pilot study, the Van5 group had less infection (0/6 infected) as compared to the Gel group (5/5, p = 0.000) and the in vivo model was deemed suitable. In the main study, in the Van2 and Van5 groups, the number of infected animals was lower [1/6 (p = 0.006) and 2/6 (p = 0.044) infected, respectively]. In contrast, BAG and NAC groups showed no infection reduction (5/6 both groups, p = 0.997). The hydrogel can be used as a local carrier of vancomycin for prophylaxis of implant-related infections. The present study showed promising results for local delivery of antibacterial agents by hydrogel to prevent implant-related infections.
Gesehen am 08.06.2020